The Fulfillment of The Clarity Principle Towards the Formulation Arrangement in The Recognition of Statutory Bodies Within the Limited Liability Company - Sri Kusuma dewi, Amelia; Anindita Purnama Ningtyas (Jurnal IUS Kajian Hukum dan Keadilan, 2023)
For a legal entity, legality is the most important element, because it indicates a state of legality or legitimacy so that it is recognized by law and society as a legal subject. Limited Liability Company, requires a special establishment procedure to legalize legal entity status, as stated in Article 109 number 2 Law Number 6 of 2023 concerning Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation to become Law which has changed the arrangements regarding the establishment of a Limited Liability Company which was previously regulated in Article 7 of the Law Number 40 of 2007 concerning Limited Liability Companies. After the amendment, the arrangement regarding the acquisition of Limited Liability Company legal status is “after being registered with the Minister and obtaining proof of registration”. The Research Team sees a legal issue, namely whether changing the arrangement meets the principle of clarity of formulation as stipulated in Article 5 letter f of Law Number 12 of 2011 Concerning the Establishment of Legislation. Furthermore, the Research Team also analyzed the proper legal reconstruction in the regulation regarding the acquisition of Limited Liability Company Legal Entity status, so that the principle of clarity of formulation was fulfilled as one of the principles for the Formation of good Legislation. This research is a type of normative juridical research using statutory and conceptual approaches. Based on the analysis of the Research Team, the arrangement regarding the time of acquiring the legal status of a Limited Liability Company does not meet the clarity principle of the formulation. While the proper legal reconstruction is to provide a formulation that uses a choice of words or terms, as well as the clarity of legal language in which understandable so that it minimizes the excessive interpretations in its implementation.